Macular Edema: The Current Recommendations for Clinical Practice - Maciej, Gawęcki (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book contains nine articles on the subject of diagnosis and treatment of macular edema due to different causes. It presents both reviews of current recommendations of macular edema treatment as well as original research on specific forms of that entity.